2019
DOI: 10.1186/s12962-019-0192-5
|View full text |Cite
|
Sign up to set email alerts
|

When donor funding leaves: an interrupted time-series analysis of the impact of integrating direct HIV care and treatment into public health services in a region of Johannesburg

Abstract: BackgroundEarly in South Africa’s HIV response, donor-funded organizations directly provided HIV treatment through Comprehensive HIV Care, Management and Treatment sites (CCMTs), using their own and government staff. From 2012 to 2014 the donor-funded CCMT model was phased out, leaving nurses in South Africa’s public clinics responsible for delivery of antiretroviral treatment (ART) services. We aimed to examine the impact on resources, staff workloads, and service delivery throughout this period of integratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…[17] Literature on the impact of the PEPFAR transition in SA has found varying outcomes. Lince-Deroche et al [18] looked at HIV service delivery post PEPFAR in three clinics in Johannesburg and found no reduction in service delivery post PEPFAR, while Cloete et al [14] found 20% loss to follow-up (LTFU) of patients transferred from private to government health facilities. Katz et al's [17] qualitative study found that patients who were transferred to the public system were frustrated owing to long queues and missed work opportunities, and decreased quality of care, highlighting disrespectful staff, 'low quality communication' and lack of holistic care.…”
Section: Researchmentioning
confidence: 99%
“…[17] Literature on the impact of the PEPFAR transition in SA has found varying outcomes. Lince-Deroche et al [18] looked at HIV service delivery post PEPFAR in three clinics in Johannesburg and found no reduction in service delivery post PEPFAR, while Cloete et al [14] found 20% loss to follow-up (LTFU) of patients transferred from private to government health facilities. Katz et al's [17] qualitative study found that patients who were transferred to the public system were frustrated owing to long queues and missed work opportunities, and decreased quality of care, highlighting disrespectful staff, 'low quality communication' and lack of holistic care.…”
Section: Researchmentioning
confidence: 99%
“…Donors (financial, material) and volunteers (medical, others) both contribute to the success of the program. The expectations of both groups should be known before they participate to avoid disappointment in the outcomes and program funding removed [26]. Donors should be briefed on the reality of the situation on the ground so that their expectations align with those of the visiting team.…”
Section: Donors and Volunteersmentioning
confidence: 99%